Purification and biochemical characterisation of acid phosphatase-I from seeds of Nelumbo nucifera. Issue 5 (3rd March 2016) - Khan, Sanaullah; Khan, Shahnaz; Batool, Sajida; Ahmed, Mushtaq
Abstract : Acid phosphatase-I (Apase-I) from seeds of Nelumbo nucifera was purified to electrophoretic homogeneity by combination of ammonium sulfate precipitation, size-exclusion and ion exchange chromatography. SDS-PAGE of purified Apase-I gave a single band with molecular mass of 80 kDa under reducing and non-reducing conditions, indicating that the enzyme was a monomer. The purified enzyme showed maximum activity at 50°C and at pH 5. The Km, Vmax and Kcat for p -nitrophenyl phosphate were 132 μM, 10 μmol/min/mg and 6.7/sec respectively. Apase-I activity was strongly inhibited by Zn 2+, W 2+ ; weakly inhibited by Cu 2+, Mo 2+ and Cr 6+ and moderately activated by Mg 2+ . The enzyme was shown to be thermolabile as it lost 50% of its activity at 50°C after incubation for 1 hour. The amino acid analysis of enzyme revealed high proportion of acidic amino acids, which is very similar to that of tomato Apase-I and lower than potato Apase. Abstract :